Data Collection and Analysis in Social Anxiety VR Therapies - Bartyna, Waldemar; Stępniak, Marcin (Studia Informatica. System and information technology, 2025)
Virtual reality (VR) therapy has emerged as a promising approach for treating social anxiety disorder by allowing controlled exposure to anxiety-provoking social situations in a safe virtual environment. Collecting and analyzing physiological data from participants during VR therapy sessions is crucial for monitoring their anxiety levels, tailoring the therapy, and assessing treatment outcomes. This article discusses the challenges and solutions for collecting and analyzing rapidly generated physiological data, such as galvanic skin response, heart rate, and respiration rate, in the context of social anxiety VR therapies. It explores techniques for real-time data streaming, storage in efficient file formats like Apache Parquet, and subsequent analysis of the collected data. The article also examines the role of data analysis in improving therapy protocols, personalizing treatment, and advancing our understanding of the physiological responses associated with social anxiety. By leveraging modern data engineering practices, VR therapy platforms can unlock valuable insights and enhance the effectiveness of exposure-based interventions for social anxiety disorder.